2022
DOI: 10.3390/plants11030281
|View full text |Cite
|
Sign up to set email alerts
|

High-Purity Preparation of Enzyme Transformed Trans-Crocetin Reclaimed from Gardenia Fruit Waste

Abstract: The recovery of physiologically bioactive ingredients from agricultural wastes as an abundant and low-cost source for the production of high value-added mutraceuticlas has been recognized and supported for the commercial interests and sustainable managements. In the extraction of geniposide for the development of natural food colorants from the dried fruits of Gardenia jasminoides Rubiaceae, the gardenia fruit waste (GFW) still remaining 0.86% (w/w) of crocins has always been discarded without any further trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…The whole gardenia fruit contained moisture of 5.53 ± 0.19%, crude fat of 19.99 ± 0.92%, crude protein of 9.97 ± 0.58%, cellulose of 14.11 ± 0.57%, pectin of 14.29 ± 0.57%, geniposide of 6.32 ± 0.17% and crocin of 9.56 ± 0.13%. The nutritional composition was similar with those reported by Chyau et al (2022). After the removal of shell, the contents of moisture, fat, protein, geniposide and crocin in gardenia seed were increased to 6.04 ± 0.14%, 24.92 ± 0.06%, 11.79 ± 0.16%, 7.68 ± 0.06%, and 10.45 ± 0.07%, while cellulose and pectin decreased to 11.93 ± 0.29% and 11.74 ± 0.24%, indicating that the lipids, geniposide and crocin tend to be enriched in the gardenia seeds, the peel is abundant of cellulose and pectin.…”
Section: Nutritional Composition Analysis For Gardenia Fruits and Gar...supporting
confidence: 89%
See 1 more Smart Citation
“…The whole gardenia fruit contained moisture of 5.53 ± 0.19%, crude fat of 19.99 ± 0.92%, crude protein of 9.97 ± 0.58%, cellulose of 14.11 ± 0.57%, pectin of 14.29 ± 0.57%, geniposide of 6.32 ± 0.17% and crocin of 9.56 ± 0.13%. The nutritional composition was similar with those reported by Chyau et al (2022). After the removal of shell, the contents of moisture, fat, protein, geniposide and crocin in gardenia seed were increased to 6.04 ± 0.14%, 24.92 ± 0.06%, 11.79 ± 0.16%, 7.68 ± 0.06%, and 10.45 ± 0.07%, while cellulose and pectin decreased to 11.93 ± 0.29% and 11.74 ± 0.24%, indicating that the lipids, geniposide and crocin tend to be enriched in the gardenia seeds, the peel is abundant of cellulose and pectin.…”
Section: Nutritional Composition Analysis For Gardenia Fruits and Gar...supporting
confidence: 89%
“…Various physiological function has been reported, including anti-in ammatory, antioxidant properties, anti-hypertension, anti-hyperglycemia, anti-cancer, anti-hyperlipidemia, neuroprotection and hepatoprotection. Furthermore, the crude fat content takes up nearly 20% of the dried fruit, and its oil level is equivalent to that of soybean, which can be applied to oil production (Chyau et al, 2022;Yin and Liu, 2018). According to previous study, gardenia oil containing plenty of Unsaturated fatty acids, particularly palmitic acid and linoleic acid, which exhibits pharmacological effects on regulating blood pressure, body fat metabolism, and reducing serum cholesterol (Cai et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…By precisely controlling the glycosylation time course, a high concentration of crocin with a specific degree of glycosylation can be obtained. Further optimization of gardenia UGTs may provide a valuable tool for the industrial production of crocin [126]. At the same time, Pu et al also found that the glucose content in the culture environment is one of the key factors for obtaining crocin.…”
Section: Biosynthesis Of Crocins In E Colimentioning
confidence: 99%
“…However, the excessive separation time (450 min) caused partial conversion of the trans-crocetin, resulting in only 85% purity. Chyau et al [18] also employed CPC for the high-purity preparation of enzyme-transformed trans-crocetin. However, before the crude sample was loaded into the CPC system, it needed to be prepurified by the macroporous resin (HPD-100).…”
Section: Introductionmentioning
confidence: 99%
“…Chyau et al. [18] also employed CPC for the high‐purity preparation of enzyme‐transformed trans ‐crocetin. However, before the crude sample was loaded into the CPC system, it needed to be prepurified by the macroporous resin (HPD‐100).…”
Section: Introductionmentioning
confidence: 99%